Determination of Labile Cadmium in Soils Using a New Sodium Alginate‐Polyglutamic Acid‐Diffusive Gradient in Thin Films. (29th April 2021) - Chen, Rui; Wang, Qi; Ren, Fumin; Ding, Guoyu; Shi, Rongguang; Cheng, Jing; Cai, Xuying; Cheng, Nuo; Liu, Jiaxing; Li, Lanxin
Abstract: Sodium alginate‐polyglutamic acid was used to develop a new diffusive gradient in thin films (SA‐PGA‐DGT) device, which was proven to be suitable for the investigation of labile Cd in soil. The adsorption capacity of Cd was calculated to be approximately 16.8 μg/cm 2, which was hardly affected by factors including pH (5–9), ionic strength (0.1–100 mM), and the presence of other metals (Pb, Cu, Ni, and Cr). The SA‐PGA gel has dense and uneven pores with large specific surface area, which ensures the adsorption of Cd by functional groups of the gel. A kinetics study indicated that the adsorption rate of Cd by the binding gel can be described as a pseudo‐second‐order reaction. Deployment of the SA‐PGA‐DGT in the soils of Tang Gu (located in Binhai New District, Tianjin, China) showed a strong positive linear correlation between Cd measured by the device and exchangeable Cd measured by the Tessier method ( R  = 0.73, p  < 0.01). Cadmium determined by the SA‐PGA‐DGT device was less affected by soil properties. This new SA‐PGA‐DGT has obvious advantages over other methods in respect of the labile Cd analysis in soil. The innovative novel device expands the variety of existing DGT technologies and can be utilized to monitor the level of labile Cd in soil effectively. Environ Toxicol Chem 2021;40:1559–1569. © 2021 SETAC